2020
DOI: 10.34218/ijmet.11.12.2020.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tyre Unbalance on Performance of Vehicle

Abstract: Now a days automobiles play a significant role in our day to day life, but automobile vehicles (cars) also need proper care and service to get optimum performance from them. Balancing technology is one of the important aspect of automobile vehicle and unbalance in tyres of vehicle plays an important part in vehicle performance.Of course, it's natural for any rotating component to vibrate. Even in the best of operating condition vehicle will have some minimum vibration because of small, minor defects. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In addition, the parallel misalignment has more considerable energy losses than angular misalignment (Abouelanouar et al ., 2020). Another study revealed that an unbalanced pump reduced the flow rate by 2.4% and the pump's power by 5% (Taneja, 2013). Besides misalignment and unbalanced, wear is also a source of energy losses caused by lubricant quality or long duration of use.…”
Section: Maintenance Strategies and Energy Efficiencymentioning
confidence: 99%
“…In addition, the parallel misalignment has more considerable energy losses than angular misalignment (Abouelanouar et al ., 2020). Another study revealed that an unbalanced pump reduced the flow rate by 2.4% and the pump's power by 5% (Taneja, 2013). Besides misalignment and unbalanced, wear is also a source of energy losses caused by lubricant quality or long duration of use.…”
Section: Maintenance Strategies and Energy Efficiencymentioning
confidence: 99%
“…Excessive wheel unbalance generates vibrations that are transmitted to the adjacent components. As a result, they cause accelerated wear to the tyres, bearings, suspension, and steering components, while also reducing driving comfort [21,23]. From the driver's point of view, wheel unbalance is usually revealed by steering wheel vibration, which is more pronounced at higher driving speeds.…”
Section: Introductionmentioning
confidence: 99%